New perspectives on an old disease: proteomics in cancer research - Gallego, Oriol (BioMed Central, 2007)
A report on the American Association for Cancer Research Conference 'Advances in Proteomics in Cancer Research', Amelia Island, USA, 27 February-2 March 2007.